Specific Learning Disability and Its Newest Definition: Which Is Comprehensive? and Which Is Insufficient?. (January 2013) - Scanlon, David
The American Psychiatric Association's proposed definition of specific learning disability ("specific learning disorder") for the DSM-5 reflects current thinking and best practice in learning disabilities. It continues the core conceptualization of learning disability (LD) as well as proposes identification criteria to supplant the discredited aptitude–achievement discrepancy formula. Improvements can be found along with long-standing and new controversies about the nature of LD. The proposed definition both provides a model of a currently acceptable definition and reflects critical issues in the operationalization of LD that the field continues to neglect.